Eyelid Complications Associated with Surgery for Periocular Cutaneous Malignancies - Carniciu, Anaïs L.; Jovanovic, Nina; Kahana, Alon (Facial Plastic Surgery, 2020)
Periocular skin is highly prone to malignancies, especially basal cell and squamous cell carcinomas. Because of the complex anatomy and eye-protecting functions of the periocular tissues, treatment of these cancers requires special considerations. Mohs micrographic surgery is usually the treatment of choice, whenever possible, in order to enhance margin control while limiting collateral damage to nearby normal structures. Cancer excision, whether by Mohs or other techniques, will leave a complex defect that requires careful anatomical and functional reconstruction. This study presents some of the challenges of treating periocular skin cancer and associated reconstructive surgery and provides an intellectual framework for addressing these challenges. The key topics are adherence to anatomical landmarks and aesthetic units, proper distribution of tension, and matching the correct reconstructive approach, that is, type of flap or graft, to the defect at hand. This review is not meant to be exhaustive, but it will provide both basic and advanced considerations.
Keywords: eyelid; basal cell; squamous cell; Mohs; eyelid retraction